New Drugs for the Treatment of DME and the Role of Biomarkers in Predicting Their Effectiveness - M. V. Budzinskaya; A. A. Plyukhova (Oftalʹmologiâ)
Today, between 230 and 347 million people on the planet suffer from diabetes, which is approximately 6 % of the all adult population. Diabetic macular edema (DME) can occur at any stage of diabetic retinopathy (DR), and remains the most common cause of moderate vision loss in patients with DR, due to increased retinal vascular permeability leading to accumulation of extracellular/intracellular fluid and blood plasma components in the neurosensory retina. The use of objective, quantifiable medical signs, called biomarkers, has become more relevant in clinical practice and clinical research. They allow the identification of a normal biological or pathological process, becoming clinical and diagnostic tools in routine clinical practice. Over the past decade, there has been significant progress in the treatment of macular edema, but the search for a more effective method does not stop. Modern research is being carried out in the direction of creating new drugs and increasing the intervals between injections. New molecules target previously studied as well as new targets. The pharmaceuticals used are investigating at higher doses and different delivery methods. Viral vectors and new phototherapeutic agents are currently being tested. This wide range of research studies, with several therapeutics currently in phase 3, could lead to impressive results in the treatment of diabetic retinopathy in the not too distant future.